2015
DOI: 10.1038/ncomms9912
|View full text |Cite
|
Sign up to set email alerts
|

Upper Palaeolithic genomes reveal deep roots of modern Eurasians

Abstract: We extend the scope of European palaeogenomics by sequencing the genomes of Late Upper Palaeolithic (13,300 years old, 1.4-fold coverage) and Mesolithic (9,700 years old, 15.4-fold) males from western Georgia in the Caucasus and a Late Upper Palaeolithic (13,700 years old, 9.5-fold) male from Switzerland. While we detect Late Palaeolithic–Mesolithic genomic continuity in both regions, we find that Caucasus hunter-gatherers (CHG) belong to a distinct ancient clade that split from western hunter-gatherers ∼45 ky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
361
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(408 citation statements)
references
References 50 publications
(135 reference statements)
30
361
1
1
Order By: Relevance
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%
“…The Yamnaya culture, associated with late Proto-Indo-Europeans, emerged during this time period in the Southwestern Siberian Ural region and the Pontic steppe region of Southeastern Europe (Allentoft et al 2015;Haak et al 2015;Jones et al 2015). Yamnaya steppe herders, who traced their origins to Eastern European and Caucasus hunter-gatherer groups, had largely replaced the Neolithic farming culture in Eastern Europe.…”
mentioning
confidence: 99%
“…Additionally, Jones et al (53) showed that the other half of the Yamnaya ancestry came from a fourth source population: the "Caucasus hunter-gatherers" (CHG), who split from the WHG ∼45,000 y ago and from the EEF ∼25,000 y ago. At present, it appears that western Eurasian populations are mixtures of four ancestral sources (ANE, EEF, WHG, CHG).…”
Section: Adna From Modern Humansmentioning
confidence: 99%